Risk Factors for Type 2 Diabetes Mellitus in Women of Childbearing Age at Unaaha Public Health Center, Konawe Regency - Jayadipraja, Erwin Azizi; Natsir, Muh; Supodo, Timbul; Sukma, Komang Ayi (Public Health of Indonesia, 2025)
Introduction: The prevalence of DM at the Unaaha Health Center in 2017 was 1.12 per 1000 population, increased by 2018 to 2.4 per 1000 population and increased in 2019 by 4.6 per 1000 population. The purpose of this study was to determine the risk factors for the incidence of type 2 diabetes mellitus in women of childbearing age at the Unaaha Public Health Center. Methods: This type of research is quantitative with a case control study design. The population is all women of childbearing age who as 378 people. The case sample is women of childbearing age who suffer from DM as many as 62 people taken by simple random sampling technique and the control sample is women of childbearing age who does not suffer from DM as many as 62 people taken by matching technique. Data analyzed by Chi-square test and Odd Ratio (OR) test. Results: The results of the chi-square test and OR for obesity p-value of 0.001 < (0.05) and OR = 3.561, for eating habits obtained p-value of 0.004 < (0.05) and OR = 3.214 as well as for blood pressure obtained p-value 0.000 < (0.05) and OR = 6.741. Conclusion: Obesity, eating habits, and blood pressure are risk factors for type 2 diabetes. Suggestions for the next researchers to conduct experimental research by implementing innovations that can reduce blood pressure and blood glucose levels in patients with Type 2 Diabetes Mellitus.